If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(x + 4) = 2x + 4 Reorder the terms: 5 + -1(4 + x) = 2x + 4 5 + (4 * -1 + x * -1) = 2x + 4 5 + (-4 + -1x) = 2x + 4 Combine like terms: 5 + -4 = 1 1 + -1x = 2x + 4 Reorder the terms: 1 + -1x = 4 + 2x Solving 1 + -1x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + -1x + -2x = 4 + 2x + -2x Combine like terms: -1x + -2x = -3x 1 + -3x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + -3x = 4 + 0 1 + -3x = 4 Add '-1' to each side of the equation. 1 + -1 + -3x = 4 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 4 + -1 -3x = 4 + -1 Combine like terms: 4 + -1 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| 4(-9a-4)+8= | | 6=-7f+4 | | 3.7+1.2=6 | | -32=-5k+13 | | sqrt(13-4z)=z-4 | | 12+4x=2(3x-4) | | 5x-2m+3x+4m= | | -4x^2+60x+900=0 | | 1/19+m=1/19 | | x^2+5x-80=0 | | -(-4-3n)= | | 8y+3=44 | | 2x=6+6 | | 2x+17=5x+8 | | -6.5=p+2.1 | | 0.25-0.4=0.15y+1-0.6y | | 10=.28571j+4 | | 7/2+1 | | 250/0.1 | | -1/2(8x+4)+1/9(54x+45)= | | -1/2x+3/7=5/7 | | -3/2-(-2+n)=-5+5n/2 | | 50m+100=100m+50 | | 1/2*3.14 | | 3h-2h+3h+m+2m= | | (2x^3)-18x+1=0 | | x^4-4x^2+14=0 | | 5*1/2+1 | | 6n-4=-22+3n | | 1/2(6x+10)+2=-20 | | -1/2+3/7=5/7 | | 3+x=31/8 |